Unravelling imaginaries of the digital divide among indigenous communities in Taman Negara Malaysia - Abadi, Mansurni (C-DISC, 2024)
The digital divide is frequently conceptualized as a disparity between those who possess access to contemporary technologies and those who lack such access. This divide is often defined by factors such as physical access, technological proficiency, and disparate outcomes. However, this perspective frequently neglects its historical origins in the